2011
DOI: 10.1002/mds.23841
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscle belly and tendon stiffness in patients with Parkinson's disease, as measured by myotonometry

Abstract: Patients with Parkinson's disease have higher passive stiffness of the muscle belly and tendon than healthy matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 26 publications
5
53
1
1
Order By: Relevance
“…Marusiak et al [24] concluded that myotonometer is a sensitive tool to assess passive stiff ness of muscles in patients with Parkinson's disease as compared with healthy controls. Patients with Parkinson's disease have higher values of passive stiff ness of the muscle belly and tendon [25].…”
Section: Discussionmentioning
confidence: 99%
“…Marusiak et al [24] concluded that myotonometer is a sensitive tool to assess passive stiff ness of muscles in patients with Parkinson's disease as compared with healthy controls. Patients with Parkinson's disease have higher values of passive stiff ness of the muscle belly and tendon [25].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in muscle tone and properties could be used to assess effects of pathology [7,12], sport-related injury [25] or therapeutic intervention [14,20]. Such assessments could be performed at regular intervals to monitor the stage of the pathological processes of muscles [19] and for assessing efficacy of therapeutic interventions [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, MAS results lack objective grading and reliability [5,16] and are not well correlated with muscle stiffness after stroke [3]. To meet this need, a novel approach, myometric measurement, has been introduced showing reliable [2,4,15], objective and user independent measurements [1, 10,22] for healthy adults [8] as well as for various patient populations, including Parkinson's disease [13,21] and stroke [6] patients. As well as being used to evaluate the tone and biomechanical properties of muscles and tendons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The MyotonPRO is a small, non-invasive, handheld myotonometer that provides an objective measure of the mechanical properties of in vivo muscles. 26 To date, the device has shown good validity [27][28][29] and high reliability [30][31][32][33] when used with the larger muscles of the upper and lower limbs.…”
mentioning
confidence: 99%